PENINGKATAN KETERAMPILAN MOTORIK HALUS ANAK DENGAN KEGIATAN KOLASE BAHAN DAUN KERING DI KELOMPOK B TK PUSAKA INDAH SAMARINDA TAHUN AJARAN 2017-2018 - Sariyem - Sariyem; Mahkamah - Brantasari; Harry - Gunawan (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2019)
Students in Pustaka Indah Kindergarten Samarinda were considered having low sensory motor skill due to lack of physical practic, unattactive facilities of learning, less maximum guide frorm the teacher, and less various teaching method. Responding the issue, the researcher applied a classroom action research to improve student’ motor skill through collage activity by using dried leaves. This study involved 20 students of Group B at Pustaka Indah Kindergarten as the research subject. Moreover, observation sheets and documentation of learning activity were employed to collect the data. The data was then analyzed through descriptive quantitative and qualitatively. The research was carried out in three cycles, wherein each cycle consists of four stages; planning, implementation, observation and reflection. Having analyed the data, students’ sensory motor skill increased after implementing the collage activity. Based on observation sheet on the students’ average score in pre cycle, 0% students did not reach the passing grade. However, at the first cycle, 40% students managed to improve their sensory motor skill, which then increased in the second cycle, making up 70,33% with good category. In conclusion, the collage activity has effectively improved students’ sensory motor skill, especially for students in Pusaka Indah Kindergarten Samarinda.